Indebtedness of small and medium-sized wineries in Slovakia - Jana Ladvenicová; Dominika Čeryová; Iveta Košovská; Jozef Palkovič; Matej Čereš (Agricultural Economics (AGRICECON))
Many companies depend on debt sources; they use them to finance their needs. Bank loans are the main debt sources to which companies have access. However, financing only with this source is associated with many risks. The paper's main goal is to assess and quantify the indebtedness of wineries in Slovakia for 2013-2021 through individual debt ratios. The influence of financial leverage on return on equity (ROE) was tested. The data were drawn from the Register of Financial Statements. From the point of view of the total debt ratio, wineries show values higher than 65%. The presence of short-term debts, especially short-term liabilities, prevailed. The average share of equity reached a very low value of 11%. The average share of bank loans on financing operating activities was very low at the level of 8.53%. The return on assets (ROA) was lower than the cost of debt in most wineries, which means that increasing indebtedness had a negative effect on ROE.